PERAN SERTA ONDOFOLO DALAM GANTI RUGI TANAH UNTUK KEPENTINGAN UMUM YANG BERKEADILAN - Retno Mumpuni; Imam Koeswahyono; Rachmad Syafaat (Universitas Negeri Malang, 2017)
Abstract: This paper aims to describe the process of compensation in the procurement of land for the public interest in the expansion of Sentani Airport, the legal implication that Ondofolo is not involved in the process of providing compensation for the procurement of land for public purposes, and the correct way of putting the role or position of Ondofolo in procurement of land for the just public interest. The study used a sociological juridical approach. The process of providing compensation in the procurement of land for public purposes in the expansion of a sentani airport involves ondofolo. The legal implications if Ondofolo not involved in the process of compensation for land acquisition for public purposes is a violation of the provisions of Article 43 of Law No. 21 of 2001 on Special Autonomy for Papua which has resulted in the validity of the decision of the government in acquiring the land. The role of Ondofolo in the procurement of land for the public interest is limited to affect the behavior of people in order to work together in realizing mutually agreed objectives for the creation of justice and the guaranteed rights of indigenous peoples both customary and constitutional of the Republic of Indonesia as long as it does not violate the rules applicable Abstrak:Tulisan ini bertujuan untuk mendeskripsikan proses pemberian ganti rugi dalam pengadaan tanah untuk kepentingan umum dalam perluasan Bandar Udara Sentani, implikasi hukum jika Ondofolo tidak dilibatkan dalam proses pemberian ganti rugi atas pengadaan tanah untuk kepentingan umum, dan cara yang benar dalam meletakkan peran atau posisi Ondofolo dalam pengadaan tanah bagi kepentingan umum yang berkeadilan. Kajian menggunakan pendekatan yuridis sosiologis. Pproses pemberian ganti rugi dalam pengadaan tanah untuk kepentingan umum dalam perluasan bandar udara sentani melibatkan ondofolo. Implikasi hukum jika Ondofolo tidak dilibatkan dalam proses pemberian ganti rugi atas pengadaan tanah untuk kepentingan umum adalah pelanggaran terhadap ketentuan Pasal 43 UU Nomor 21 Tahun 2001 tentang Otonomi Khusus Papua yang mengakibatkan tidak sahnya keputusan pemerintah dalam pengadaan tanah tersebut. Peran Ondofolo dalam pengadaan tanah untuk kepentingan umum adalah sebatas mempengaruhi tingkah laku orang-orang supaya dapat bekerja sama dalam mewujudkan tujuan yang disepakati bersama demi terciptanya keadilan dan terjaminnya hak-hak masyarakat adat baik secara adat maupun secara konstitusional Republik Indonesia selama tidak melanggar aturan yang berlakuDOI : http://dx.doi.org/10.17977/um019v2i12017p064